Circadian Rhythm Disruption and Sepsis in Severe Trauma Patients. Issue 1 (July 2019) - Coiffard, Benjamin; Diallo, Aissatou B.; Culver, Aurélien; Mezouar, Soraya; Hammad, Emmanuelle; Vigne, Coralie; Nicolino-Brunet, Corine; Dignat-George, Françoise; Baumstarck, Karine; Boucekine, Mohamed; Leone, Marc; Mege, Jean-Louis
ABSTRACT: Background: Circadian rhythms are important regulators of immune functions. Admission to an intensive care unit may impact molecular clock activity and host response. Our objective was to assess and compare the immune circadian rhythms in trauma patients who develop and in those who do not develop sepsis. Methods: Blood samples were collected from severe trauma patients within 4 days after admission, with collections taking place every 4 h over a 24-h period. Cortisol and cytokines were measured with immunoassays. Whole-blood expression of 3 clock genes ( Bmal1, Per2, and Per3 ) was studied by reverse transcription quantitative polymerase chain reaction. Neutrophils, monocytes, and lymphocytes were analyzed by flow cytometry. Patients with and without sepsis were compared with the cosinor mixed model to estimate mesors, amplitudes, and acrophases. Results: Thirty-eight patients were enrolled in the study, and 13 developed at least 1 septic episode. The septic patients had higher levels of cortisol than the nonseptic patients (mesor at 489 nmol/L vs. 405 nmol/L, P  < 0.05) and delayed acrophases (22 h vs. 15 h, P  < 0.05). They also had lower lymphocyte counts (mesor at 785 vs. 1, 012 cells/μL, P  < 0.05), higher neutrophil counts (mesor at 7, 648 vs. 7, 001 cells/μL, P  < 0.05), and monocyte counts (mesor at 579 vs. 473 cells/μL, P  < 0.05) than the nonseptic patients. Although no amplitude difference was identified, the acrophases were significantly different between the 2 groups for lymphocytes, interleukin 10 and tumor necrosis factor. Conclusion: We demonstrated that all trauma patients had impaired circadian rhythms of cortisol, cytokines, leukocytes, and clock genes. Early circadian disruption was associated with the occurrence of sepsis and might be a marker of sepsis severity. Abstract : Supplemental Digital Content is available in the text